Detailed Visualization of Aromaticity Using Isotropic Magnetic Shielding. Issue 43 (24th August 2020) - Lampkin, Bryan J.; Karadakov, Peter B.; VanVeller, Brett
Abstract: For many years, Clar's aromatic sextet theory has served as a qualitative method for assessing the aromatic character of polycyclic aromatic hydrocarbons. A new approach, based on the calculation of isotropic magnetic shielding (IMS) contour plots, is shown to provide a feature‐rich picture of aromaticity that is both quantitative yet still easily interpreted. Chemists are visual creatures who are adept at discerning reactivity and chemical behavior from molecular structures. To quote Roald Hoffmann, "People like pictures. Chemists live off them." Thus, the detailed image analysis we present simultaneously provides quantitative assessment of electronic structure, which is still easy‐to‐understand through visual inspection, embedded in an aesthetically appealing and intuitive picture that draws the reader in. We provide novel computed IMS contour plots for a representative selection of aromatic molecules. Where Clar's static drawings capture only a partial sketch of the electronic properties of a molecule, IMS contour plots present a detailed, global landscape of a molecule that sums all possible resonance structures. This novel analysis allows us to correct certain drawbacks of Clar's analysis with respect to polycyclic aromatics and quantitatively assess the bonding and electronic structure of acene hydrocarbons. Abstract : A cartoonish Greek god Janus looks into the past at Erich Clar's aromatic sextet theory, which provided only a qualitative visual inspection of a single aspect of electronic structure—aromaticity. A more detailed face of Janus looks forward to a future in which the aromatic properties of molecules can be visually inspected for quantitative information using isotropic magnetic shielding contour plots.